Process Genre Based Approach (PGBA) To Academic Short Essay Writing Learning In the Context of EFL Classroom - Harpiansi, Harpiansi (JURNAL ILMU PENDIDIKAN, 2023)
Writing English academic writing is still the most specter constraint for all over Indonesian EFL college students. These is caused by the complexities of academic writing containing mechanics, vocabulary, content, organization, grammar and sentence structure, as well as writing steps; planing, drafting, editing, and revising which makes it challenges. Another reason why writing academic essay is challanges for students is that the characteristics of academic writing are clear, concise, focussed, structured and backed up by evidence. Its purpose is to aid the reader's understanding. It has a formal tone and style. Process Genre-Based Approach (PGBA) is a problem shooter offered to overcome the students’ problem. The purpose of the study was to determine whether the ability of the fourth semester students of Class D of the English Education Study Program of the Foreign Language Academy of Indonesian Development in writing English essays through the Application of the Process Genre-Based Approach (PGBA) would increase or not. The design of this research is pre-experimental-one group pretest posttest. The population is semester IV (even) students for the academic year 2021/2022. The research sample is class students who are determined by using the total sampling technique. Data collection techniques were carried out using tests: pretest (Pretest) and final test (Posttest). The treatment was carried out 6 times. The results of the data were analyzed statistically. The results showed that the posttest average score (70.7) was greater than the pretest average (55.67). This indicates that the semester students' ability to write English essays through the Application of the Process Genre-Based Approach (PGBA) increased. The results of this study are very useful for: (1) students to improve their essay writing skills; (2) teachers (lecturers) to add an approach to learning to write essays through PGBA with (a) preparation stages; (b) modeling and reinforcing; (c) planning; (d) joint construction; (e) independent constructing; and (f) revising. (3) English lecturers and teachers can conduct classroom action research using PGBA.